A Literature Review on Integrated Resource Management ( IRM ) - Yudoko, Gatot (SBM ITB, 2006)
This paper is aimed at outlining a literature review on integrated resource management (IRM). The literature review highlight IRM from three views, namely conceptual perspective, methodological perspective, and implementation perspective. Our critical discussion of IRM leads us to a conclusion that considering the various applications of IRM, we propose that it is time to change the label of IRM into IREM (Integrated resource and environmental management). We also propose that further work on IREM could be directed on developing an alternative analytical framework based on the cycle of management processes as well as developing a more operational framework to implement IREM.